Changes in Phenotypes and DNA Methylation of In Vitro Aging Sperm in Common Carp Cyprinus carpio - Cheng, Yu; Vechtova, Pavlina; Fussy, Zoltan; Sterba, Jan; Linhartová, Zuzana; Rodina, Marek; Tučková, Vladimíra; Gela, David; Samarin, Azin Mohagheghi; Lebeda, Ievgen; Xin, Miaomiao; Zhang, Songpei; et al. (International journal of molecular sciences, 2021)
The purpose of the current study was to analyze phenotypic and functional characteristics of common carp (Cyprinus carpio) spermatozoa during in vitro aging and to investigate whether global DNA methylation is affected by sperm aging. Milt was collected from five individual males, stored in vitro on ice in a refrigerator for up to 96 h post stripping (HPS) and used to fertilize eggs with intervals of 1, 24 and 96 h. Computer-assisted sperm analysis and a S3e Cell Sorter was employed to determine the spermatozoa phenotypic characteristics (motility, velocity, concentration and viability). In addition, pH and osmolality of the seminal fluid and the capacity of the spermatozoa to fertilize, hatching rate and health of the resulting embryos were examined at different aging times. Whole-genome bisulfite sequencing was used to compare the global and gene-specific DNA methylation in fresh and aged spermatozoa. The results demonstrated that spermatozoa aging in common carp significantly affects their performance and thus the success of artificial fertilization. The methylation level at the cytosine-phosphate-guanine (CpG) sites increased significantly with 24 HPS spermatozoa compared to the fresh group at 1 HPS and then decreased significantly at 96 HPS. A more detailed investigation of gene specific differences in the DNA methylation was hindered by incomplete annotation of the C. carpio genome in the public databases.
Keywords: Aging; common carp; fertilization; mužské pohlaví; kapři; epigenetics; milt; DNA methylation; Carps; stárnutí; zvířata; sperm storage; metylace DNA; sperm quality; DNA Methylation; sperm aging; Spermatozoa; spermie; Male; fish; Animals